Postural corrections after standardised perturbations of single limb stance: effect of training and orthotic devices in patients with ankle instability. Issue 2 (June 1996) - Pintsaar, A; Brynhildsen, J; Tropp, H
Abstract : OBJECTIVE: Soccer players with functional instability of the ankle joint have shown impairment of postural control in single limb stance. The aim of this study was to examine the effect of stance perturbation. METHODS: A standardised method for the study of postural corrections after perturbation (Equitest) was used. Female soccer players with and without functional instability were examined. RESULTS: The subjects showed a relative change from ankle to hip synergy at medially directed translations of the support surface. This impairment was restored after eight weeks of ankle disk training. The effect of a shoe and brace did not exceed the effect of the shoe alone. CONCLUSIONS: Functional instability seems to be related to impaired ability to retain equilibrium in single limb stance by means of ankle corrections. A positive effect of ankle disk training leading to functional restoration was confirmed.